Molecular Dynamics of POPC Phospholipid Bilayers through the Gel to Fluid Phase Transition: An Incoherent Quasi-Elastic Neutron Scattering Study - U. Wanderlingh (Journal of Chemistry, 2017)
The microscopic dynamics for the gel and liquid-crystalline phase of highly aligned D2O-hydrated bilayers of 1-palmitoyl-oleoyl-sn-glycero-phosphocholine (POPC) were investigated in the temperature range from 248 to 273 K by using incoherent quasi-elastic neutrons scattering (QENS). We develop a model for describing the molecular motions of the liquid phase occurring in the 0.3 to 350 ps time range. Accordingly, the complex dynamics of hydrogen are described in terms of simple dynamical processes involving different parts of the phospholipid chain. The analysis of the data evidences the existence of three different motions: the fast motion of hydrogen vibrating around the carbon atoms, the intermediate motion of carbon atoms in the acyl chains, and the slower translational motion of the entire phospholipid molecule. The influence of the temperature on these dynamical processes is investigated. In particular, by going from gel to liquid-crystalline phase, we reveal an increase of the segmental motion mainly affecting the terminal part of the acyl chains and a change of the diffusional dynamics from a localized rattling-like motion to a confined diffusion.